(untitled) (Research, Society and Development, 2026)
This article aims to understand the school environment based on the perceptions of students and teachers from a public high school located in the municipality of Alterosa (MG), also considering the socioeconomic context in which the institution is embedded. The research is characterized as an exploratory case study, developed through a predominantly qualitative approach, supported by quantitative data. Data collection involved the application of questionnaires to students and teachers, as well as the use of secondary data from the Brazilian Institute of Geography and Statistics (IBGE), in order to contextualize the local reality. It is noteworthy that the study was conducted during the period of restrictions imposed by the COVID-19 pandemic, which influenced both the data collection conditions and school dynamics. The results indicate that the school is perceived as a space of coexistence grounded in dialogue, particularly in conflict mediation. However, divergences were identified in perceptions regarding structural conditions and services provided, suggesting limitations related to infrastructure and staffing. It is concluded that, although the municipality does not present indicators associated with extreme poverty, the local context reveals socioeconomic challenges that impact the school environment. In this sense, the analysis of participants’ perceptions contributes to understanding educational relationships and to reflecting on the role of the school in shaping the subject of knowledge.